EU11 Regular Economic Report, Issue #29, July 2014 : Strengthening Recovery in Central and Eastern Europe - World Bank (Washington, DC, 2014)
Economic growth is expected to almost double in EU111 in 2014, and continues to strengthen in 2015. Overall EU11 GDP growth is forecast to strengthen from 1.4 percent in 2013 to 2.6 percent in 2014. The initial reliance on net export growth, with rising demand from the rest of the EU, is gradually giving way to more balanced growth as domestic demand picks-up, notably in Romania, Slovakia and Poland. Fiscal consolidation will continue in 2014 and 2015, but at a more gradual pace than in the previous years. The overall EU11 fiscal deficit is expected to drop to 2.9 percent of GDP in 2014 and to 2.5 percent of GDP in 2015. However, there is a need for larger adjustments in Croatia and Slovenia to achieve sustainable deficit and debt levels. Economic growth forecasts in the EU11 are subject to multiple risks, mainly on the downside, as the global financial situation remains fragile. While labor market conditions have started to improve, the pace of job creation and reduction in unemployment rates are likely to be gradual.